A Systems-Theory Analysis of the Relationship between Communication, Beliefs/Practices, Religiosity, Spirituality and Expected Future Religious Practices of College Students. Issue 1 (2nd January 2022) - Williams-Smith, Rachel; McMillan, Sally J.
Abstract: This study uses systems theory to explore relationships between individual, micro, meso, and macro factors and expected future religious practices of students studying at a Seventh-day Adventist university. The study operationalizes system theory in context of both public relations and spirituality. The primary purpose is to understand relationship between each level of systems theory and students' expectations about future religious practices. Key recommendations include the need to increase use of digital communication tools, the value of distinguishing between understanding and belief/action at the micro level, and the importance of supporting spiritual development outside the context of organized religion.